ONEMATOPE BAHASA SUNDA DAN TERJEMAHANNYA DALAM BAHASA INGGRIS - Yaya Mulya Mantri (TEXTURA, 2018)
This  research  focuses  on  onomatopoeic words  consisted  in  Sundanese  poetry  and  it  translated  English.  The  Sundanese poetry  is  the  anthology  of  Sundanese  poetry:  Modern  Sundanese  Poetry  Voices from West Java  in Sundanese and English compiled by Ajip Rosidi and translated by Wendy Mukherjee. This research focuses on two problems. The  first  is  to  find  out  the  sources  (of  sounds)  of  onomatopoeic words  in  the  anthology  of  Sundanese  poetry.  The second  is  to  explore  the differences or similarities of words sounds and sources both in Sundanese and its English translated version. From the whole analysis, it concludes that Sundanese onomatopoeic words have three sources (of  sounds):  things,  animal,  and human.